EKONOMI KOLABORATIF: RELASI EKONOMI DAN HUKUM DI ERA DISRUPTIF - Holilur Rahman (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
Economic and legal collaboration as a field of life has a strategic role. As technology advances in a disruptive era, the two can influence each other. This article seeks to examine economic and legal relations as a form of collaboration in the era of disruption on several issues; basic concepts of economics and law, implementation of economic and legal collaboration, the influence of economic and legal colobaration. This study produces conclusions with three main theses, namely: first, economic regulation by law is always in two ways between the rights and obligations that are interconnected between the two. Second, the prospect of economic collaboration with the law in a potential disruptive era in terms of efficiency and effectiveness. Third, collaborative economics is in tune with the basic principles of muamalah al-maslahah especially the rules of bringing benefits and avoiding madharat, جلب المصالح ودرء المفاسد (jalb jalb al-masalih wa dar’u al-mafasid).